Acute-Onset Acquired Stuttering Secondary to Concussion: A Case Report. - Wagner, Kelsey Jo; Hux, Karen (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: Acquired stuttering in young adults can present diagnostic and treatment challenges. This single case report documents the diagnosis of acquired, postconcussive, acute-onset stuttering in an 18-year-old man, describes key elements of a person-centered treatment program conducted via a telerehabilitation platform, and reports documented changes in speech production following intervention. Method: Person-centered care principles, disfluency education, strategies for managing stuttering episodes, and a home program were treatment components. Using the Overall Assessment of the Speaker's Experience of Stuttering (OASES) and speech sample analyses, documentation of initial status and changes over time came from initial, 3-month, 6-month, and follow-up evaluations. Results: Initial OASES scores were consistent with moderate--severe impact for General Information, moderate impact to Daily Communication, and mild-- moderate impact with respect to Speaker's Reactions, Quality of Life, and Overall Assessment. The initial speech sample analysis revealed severely disrupted speech production with disfluencies occurring on 60.47% of syllables. In contrast, the 6-month assessment revealed mild or mild--moderate OASES impact scores and disfluencies on 1.78% of syllables. Performance during a follow-up evaluation held 3 months following treatment termination confirmed maintenance of fluent speech production both when reading and engaging in conversation. Conclusion: Clear differentiation between neurogenic and functional contributions to acute-onset, acquired stuttering is not always possible. In some cases, a combination of precipitating factors may be evident. Regardless, presenting traditional fluency management strategies within a framework of personcentered care can be an effective treatment approach.